Optimising environmental risk assessments. (18th August 2015) - Devos, Yann; Romeis, Jörg; Luttik, Robert; Maggiore, Angelo; Perry, Joe N; Schoonjans, Reinhilde; Streissl, Franz; Tarazona, José V; Brock, Theo CM
<x xml:space="preserve">Abstract</x> Environmental risk assessments cannot cover all conceivable risks. It is therefore necessary to translate broader policies such as sustainable development into specific protection goals with the overall aim of protecting biodiversity and maintaining ecosystem services. <boxed-text content-type="graphic" id="embr201540874-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>